FORMULATION AND EVALUATION OF BILAYER TABLETS OF LIMEPIRIDE AND CAPTOPRIL - J. AISHWARYA; N. SRINIVAS (International Journal of Pharma and Bio Sciences, 2015)
The present study is to establish bi-layer tablets of Glimepiride and Captopril, of which Glimepiride as immediate release and Captopril as sustained release layers. Immediate release layer was prepared by direct compression method by using cross povidone as disintegrant and sustained release layer was prepared by direct compression method by using HPMC K4 as polymer. Both powder blends of immediate and sustained release layers were evaluated for Bulk density, Tapped density, Compressibility index, Hausner ratio and Angle of repose. All the values were found within limit of standard. In vitro release studies were carried out by USP type 2 paddle apparatus. The result showed that polymer HPMC K4 in sustained layer controlled the release of drug. The formulation (F4) having immediate release layer produced immediate effect showing 99.6%drug release within 30minutes, followed by sustained release effect showing 96.8% drug release upto 12 hours. The present study concluded that Bilayer tablets of Glimepiride and Captopril can be a better alternative to conventional dosage form for providing immediate and sustained drug delivery.